ORBITAL COMPLICATIONS OF SINUSITIS–RETROSPECTIVE ANALYSIS - KUMAR B, AJAY; N, SUHASINI; M, Harini (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study is to consider and analyze patients who were treated for these complications in the last 2 years in our hospital, comparing with another 2 tertiary care hospitals. Methods: It is a retrospective study. Out of the total number of ear, nose, and throat ENT cases attending our outpatient department, cases treated in the hospital with rhinosinusitis where surgical intervention is necessary, or those with a suspicion of complications. Between 2017 and 2019, there were 25 cases from three tertiary care hospitals, the clinical charts of which were reviewed. Consent has been taken from all the participants. The cases that are excluded from this study are those involving soft tissues, bone, and with intracranial complications. The diagnoses were determined based on history, anterior rhinoscopy, radiological imaging of the paranasal sinuses (X-ray), or computed tomography scan taken where there was a suspicion of a complication. In all cases, intensive treatment was initiated with a combination of cephalosporins and aminoglycosides and nasal irrigation with saline sprays. Results: In our study, in GITAM Institute of Medical Sciences and Research we encountered 6 cases the average time that patients remained in hospital was 4–5 days; for those with orbital complications this was 7 days. Similarly in other two tertiary care hospitals Andhra Medical College Visakhapatnam encountered around 15 cases and Konaseema Institute of Medical Science, Amalapuram, encountered 4 cases total constituting of 25 cases. Conclusion: The appearance of edema in the corner of the eye should be evaluated immediately, and the means to exclude acute sinusitis should be taken under serious consideration. Early diagnosis and aggressive treatment are important steps to be taken to avoid orbital complications like loss of vision.